A DEAL for open access: The negotiations between the German DEAL project and publishers have global implications for academic publishing beyond just Germany. (15th May 2018) - Hunter, Philip
Abstract : The German DEAL project negotiates full open access publishing with the major publishers for many academic institutions in Germany. If successful, it could have a global impact on funders' publishing policies.